How variation among field assessments can affect biodiversity offset outcomes - Peter Contos; Emma Gorrod; Karen Caves; Ian Oliver; Josh W. Dorrough (Conservation Science and Practice)
Abstract Biodiversity offsetting aims to balance biodiversity loss at development sites with gains at offset sites. Measurement of loss and gain relies on transparent and repeatable estimates of biodiversity values. However, these estimates are often derived from field assessments by people who differ in their interpretation and measurement of biodiversity, either randomly or systematically. Variation among people during field assessments may therefore impact offset outcomes and contribute to uncertainty around the effectiveness of biodiversity offset schemes. Here, we describe variation in loss, gain, and offset outcomes using concurrent assessments by five assessors on eight sites using a multi‐metric biodiversity valuation method from New South Wales, Australia. We found variation among assessors was high for field estimates but substantially decreased for current biodiversity valuations. However, variation increased for the prediction of future biodiversity gains, in the calculation of the required offset area, and contributed an average of 19% variation in development credits (biodiversity loss) and 34% variation in offset credits (biodiversity gain). Evidence of systematic bias among observers for some attributes added further uncertainty to offset outcomes. Our study reveals the need for improved assessor training and field methods to improve assessment consistency, transparency, and reduce offset outcome variability.